White Paper on Social Responsibility and Green Human Resource Management in Organization: The Implications for Moral Identity - Friscila, Angelina Sofya (Business Education Program of Universitas Pendidikan Indonesia, 2024)
This article explores the link between green and socially responsible behaviour and its impact on moral identity. It suggests that Green Human Resource Management (GHRM) and Social Responsibility positively influence moral identity formation within the workplace, primarily through internalization and symbolization processes and by encouraging moral voices from coworkers. The findings highlight the significance of fostering supportive workplace environments to cultivate morally solid identities. The discussion emphasizes how green and socially responsible behaviour can reinforce moral values in work contexts, offering insights for practitioners and researchers. The study also suggests further exploring how moral identities shaped by other norms may influence green and socially responsible behaviour. Overall, the research sheds light on the complex interplay between green behaviour, social responsibility, and moral identity, emphasizing the role of organizational environments in shaping moral behaviour.